Meta Analysis Study of Marketing Innovation on SME Business Performance in Ethiopia - Shashi Kant; Fisseha Dejene YADETE; Chalchissa Amentie KERO (RADINKA JAYA UTAMA PUBLISHER, 2023)
This study looked at how market innovation affected SMEs' performance in Addis Abeba, Ethiopia, with the use of government support programs as a moderator. The study's meta-analysis will be guided by the Schumpeter innovation theory, which also incorporates the diffusion of innovation theory, expectancy theory, institutional theory, stakeholder theory, absorptive capacity theory, resource-based view/theory, dynamic capability theory, R-A theory, and a unified theory of acceptance and use of technology. The researcher used an effect size approach based on a forest and funnel plot to scan, exclude, and include relevant material. Researchers discovered a connection between the dimension of innovation and company performance on the basis of an extensive literature review. Also Based on the studied literature, the researcher discovered a link between the moderation of the government support program and the performance of SMEs' firms in the area of innovation. To carry out this study, an exploratory sequential mixed-methods research design will be used. Based on the current literature, the study attempts to create a conceptual framework and testable hypotheses. It was discovered that the impact of marketing innovation on a firm's performance was moderated by government support programs. Businesses must be encouraged to adopt government support programs with a moderating influence as a result.